IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PEMBATASAN USIA PERNIKAHAN ANAK (STUDI KASUS DI DESA LAMBANGKUNING, KECAMATAN LUMBANG, KABUPATEN PROBOLINGGO) - Marwiyah, Siti; Rahmadi, Andhi Nur; Wahyuni, Nurul Tri (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
The policy of limiting the age of child marriage is an important effort to improve the quality of life of children and prevent early marriage which can have a negative impact on their health and development. This research aims to analyze the implementation of this policy in Lambangkuning Village, Lumbang District, Probolinggo Regency in 2022-2023. The research method used is qualitative with a case study approach. Data was obtained through in-depth interviews, observation and documentation. The research results show that even though the policy has been implemented, there are still challenges in its implementation, including cultural, economic factors and lack of socialization.Keywords: Implementation, Policy, Minimum Age Limit, Early Marriage